Potensi Pengembangan Jagung di Sumatera Selatan - Rudy Soehendi; Syahri Syahri (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
The demand of corn continues to increase along with the increasing of populations and industries. Compliance efforts could be done by increasing productivity through extensification and intensification farming. Statistical data showed that corn harvested area and production in South Sumatra over the period 2000-2012 was very volatile but had a tendency to increase since 2006. The area of ​​land suitable for development of corn in South Sumatra, which amounted to 898,877 ha. This area consists of the intensification of land (205,709 ha), extensification of land (159,444 ha) and the diversification of land (533,724 ha). Land use for corn so far has been done in some districts/cities having dry land like Ogan Komering Ulu (OKU), OKU Timur, Ogan Ilir, Ogan Komering Ilir well as in several districts that have ups and downs like agro Banyuasin and Musi Banyuasin. South Sumatra AIAT demonstration plots showed that significant productivity of corn. In 2010, IPM demplot of Mulyasari village, sub district of Tanjung Lago, District of Banyuasin showed that productivity of Bima 4 (8.8 t/ha), Bima 5 (8.3 t/ha), and Bisi 2 (8.4 t/ha), whereas in 2011 Banyuurip demplot showed that productivity of Bima 3 (11.27 t/ha) and Sukmaraga (8.13 t/ha).